Structural and functional connectivity correlates with motor impairment in chronic supratentorial stroke: a multimodal magnetic resonance imaging study. Issue 7 (1st May 2019) - Lee, Jang Ho; Kyeong, Sunghyon; Kang, Hyunkoo; Kim, Dae Hyun
Abstract : The aim of this study was to identify differences in structural and functional brain connectivity between poststroke mild and severe motor impairment. Twenty-four chronic stroke patients who underwent resting-state functional MRI and diffusion tensor image were retrospectively included. All patients were classified into two groups (mild motor impairment: 11 patients and severe motor impairment: 13 patients) according to their Fugl-Meyer motor assessment score. Tract-based spatial statistics and group independent component analyses were applied to investigate between-group differences in structural and functional connectivity, respectively. The fractional anisotropy values of motor-related brain regions in the affected hemisphere were significantly higher in mild motor impairment than in severe motor impairment (corrected P <0.05). The internetwork functional connectivity between (i) the supplementary motor area and primary motor cortex in the affected hemisphere, (ii) the supplementary motor area and dorsolateral prefrontal cortex in the unaffected hemisphere, and (iii) the ischemic lesion and primary motor cortex in the unaffected hemisphere was significantly higher in mild motor impairment than in severe motor impairment ( P FWE <0.05). Better motor recovery after stroke could be facilitated by means of treatments aimed at enhancing structural and functional connectivity among motor-related brain regions such as noninvasive brain stimulation and neurodevelopmental therapy.